2010
DOI: 10.1038/nature08848
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Drosophila TRPA1 reveals an ancient origin for human chemical nociception

Abstract: Chemical nociception, the detection of tissue-damaging chemicals, is important for animal survival and causes human pain and inflammation, but its evolutionary origins are largely unknown. Reactive electrophiles are a class of noxious compounds humans find pungent and irritating, like allyl isothiocyanate (in wasabi) and acrolein (in cigarette smoke)1–3. Insects to humans find reactive electrophiles aversive1–3, but whether this reflects conservation of an ancient sensory modality has been unclear. Here we ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
329
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(345 citation statements)
references
References 37 publications
11
329
0
Order By: Relevance
“…3C) or properties of native rat snake TRPA1, which exhibits low heat and moderate AITC sensitivity (10). Indeed, this inverse relationship between thermosensitivity and chemosensitivity also pertains to invertebrate (insect) orthologs (10,12), suggesting an ancient arrangement in TRPA1 structures that has been maintained over a long evolutionary period and in the face of extensive drift in primary amino acid sequence (Drosophila and human TRPA1 share <30% sequence identity). Unlike TRPA1, TRPV1 is heat-sensitive in all vertebrate species thus far examined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3C) or properties of native rat snake TRPA1, which exhibits low heat and moderate AITC sensitivity (10). Indeed, this inverse relationship between thermosensitivity and chemosensitivity also pertains to invertebrate (insect) orthologs (10,12), suggesting an ancient arrangement in TRPA1 structures that has been maintained over a long evolutionary period and in the face of extensive drift in primary amino acid sequence (Drosophila and human TRPA1 share <30% sequence identity). Unlike TRPA1, TRPV1 is heat-sensitive in all vertebrate species thus far examined.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of the capsaicin receptor, TRPV1, suggest that the N-terminal ARD constitutes a binding site for cytoplasmic regulatory factors, such as ATP and calmodulin (17,45), consistent with our findings that the TRPA1 ARD contributes to channel modulation by environmental and endogenous agents. Several TRP channels act as polymodal signal detectors (5, 46), but TRPA1 is unique in that different species use this channel for distinct physiological purposes, generally favoring one modality (thermal or chemical) over the other (10,12). This may reflect evolutionary pressure to reduce background noise from environmental irritants in organisms in which the channel is used primarily for thermoreception, and vice versa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a parallel study, Macpherson et al [121] used click chemistry and mass spectrometry to identify 14 cysteines that can be modified by iodoacetamide (IA); three of which (C415, C422 and C622, mouse TRPA1) are critical for mediating the activating effect of mustard oil on channel function. Cysteine 622 (mTRPA1) is identical to C621 (hTRPA1) and is conserved in TRPA1 clade members with the exception of Ciona intestinales, as also C622, C415, C422, C642 and K712 (mTRPA1), suggesting an ancient shared origin of chemical nociception [122].…”
Section: Trp Channelsmentioning
confidence: 99%
“…Indeed, a recent finding has suggested that two specific GPCRs-GUR-3 and LITE-1-both of which play important roles in light sensing in C. elegans, may also be H 2 O 2 sensitive (16). Moreover, TRPA1, an evolutionarily conserved TRP channel known for its role in sensing many chemical irritants, has been shown to sense H 2 O 2 (17)(18)(19)(20)(21)(22)(23)(24), thus TRPA1 may be activated by light via sensing light-induced H 2 O 2 production. Some recent evidence has demonstrated a role for TRPA1 in light sensing.…”
mentioning
confidence: 99%